Problema fronterizo con Venezuela como una solución al narcotráfico en Colombia (2014)
in a globalized world where to communicate and conduct business there is no need for physical contact , but through communication big business are carried out and the geographical limitations no longer exist today are vital to interact and exchange and purchase products have served as a conduit for growth and development of countries, however the lack of job and opportunities , education , principles and illicit enrichment , contributed to the drug trade every day, not only nationally but also internationally , thus this conflict affects Colombia , where his image among countries is negative , as the failings of a country can achieve unbalance the economy and progress of the same. where one of the inputs and outputs of illicit business greater influence in Colombia is known on the border with Venezuela, there have been seized illicit armament residence that therefore needs more attention and investment to all matters relating to safety, training, education and effective monitoring, which does not allow the transfer of goods from the drug trade and military ties with similarly - governing employment opportunities exist